Rice Gene Pool for Tarai and Inner Tarai Areas of Nepal - Joshi, Bal K (Nepal Agriculture Research Journal, 2010)
Knowledge on crop gene pool helps to develop varieties, to know the potential sources for breeding materials and to develop strategy for sustainable use and conservation. The amount of genetic diversity presents depends on the number and diversity of the original ancestors involved in the creation of a germplasm pool, existing landraces and wild species. The objective of this research was to study the diversity of rice gene pool present in the Nepalese improved rice cultivars and landraces adapted to Tarai and Inner Tarai (<1000 m). Pedigrees of 28 Nepalese rice cultivars were examined and surveyed the literature for distribution of landraces and wild relatives of rice. Crosses among indica rice gene pool are more common and use of japonica and nivara species were less common. There are 28 improved rice cultivars, >500 landraces, and 6 wild species and relatives of rice adapted to Tarai and Inner Tarai. Eight countries are the origins for 28 cultivars. In Nepal 4 cultivars were bred and developed using a local landrace and exotic genotypes. A total of 35 ancestors originated in 11 different countries were used to develop these 28 cultivars. Highest number of ancestors was from India. Use of ancestors of both sativa and nivara species having indica and japonica types indicated the collection of wide gene pool. Most of the ancestors were sativa (60.00%) and indica (65.71%). Genetic erosion is observed in rice diversity therefore, in situ, on farm and ex situ conservations are necessary for maintaining the genetic variation. Utilization of local landraces in breeding program may be the good way of genetic resources conservation. Gene pool from these landraces along with international gene pool could make towards success in developing high yielding cultivars with wide adaptability and/or site specific. In this study, cultivars and landraces surveyed represent a wide range of variation for different areas of origin and adaptation. This genetic diversity is very useful for further rice improvement and should be conserved both ex situ and in situ. Key words: Ancestor; Landrace; Nepalese rice cultivar; Rice gene pool; Tarai and Inner Tarai DOI: 10.3126/narj.v6i0.3339 Nepal Agriculture Research Journal Vol.6 2005 pp.10-22